Control of fall armyworm with granular insecticides mechanically applied to corn and sorghum crops - Cruz, Ivan; Santos, Jamilton P.; Waquil, José M.; Bahia, Francisco G.T.F.C. (Pesquisa Agropecuaria Brasileira, 2014)
From a commercial granular insecticide applicator for soil application, it was made some adaptations to apply granular insecticides directly into the plant whorl to control the fall armyworm (Spodoptera frugiperda Smith). The machine was adapted in a cultivator so the application of nitrogen on band on the soil surface, the cultivation, and the control of the insect could be done simultaneously. Using the adapted machine, several insecticides were tested on corn and sorghum crops. With the exception of deltamethrin (5.3 grams of active ingredient/ha) and carbofuran (0.44 kg/ha) which were not efficient in controlling the insect, the other insecticides presented a percentage of control varying from 81.2 to 100%. Among them, methomyl, diazinon, forate, chlorpyriphos ethyl, fonofos, quinalphos, carbaryl and acephate were tested. Considering the advantages of granular insecticides (less hazardous to applicator, minimum drift and no water necessity) and the efficiency results obtained, it can be concluded that: the granular applicator, with the described adaptations, can be used to control fall armyworm on com and sorghum with the additional advantage of being used integrated to the operations of nitrogen application and cultivation for weeds.